2023
DOI: 10.3390/su15065112
|View full text |Cite
|
Sign up to set email alerts
|

Pro-Environmental Determinants of Waste Separation: Does the Interaction of Human and Social Capital Matter? Evidence from Italian Provinces

Abstract: Sustainable practices should include proper incentives and involve a large part of the population to achieve a significant environmental impact. Human capital is considered one of the factors that affect pro-environmental behaviours: more educated people tend to be more aware of waste management processes. Another factor is social capital, as far as the feeling of belonging to a society might involve people in adopting sustainable practices. However, these two concepts are strictly related and deserve to be st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 127 publications
0
4
0
Order By: Relevance
“…There is a need for a more comprehensive approach to waste management that takes into account social capital, community empowerment, and social entrepreneurship in current studies. This study seeks to address this gap by thoroughly investigating how these three elements interact and impact waste management techniques (Kasjono et al, 2023;Odoardi et al, 2023;Sunarti et al, 2023). This research discovered that social capital, which includes elements like community initiative, education, communication, and skill development, is significant in waste bank (WB) administration (Ramesh, 2016).…”
Section: Addressing Gaps In Existing Literaturementioning
confidence: 99%
See 2 more Smart Citations
“…There is a need for a more comprehensive approach to waste management that takes into account social capital, community empowerment, and social entrepreneurship in current studies. This study seeks to address this gap by thoroughly investigating how these three elements interact and impact waste management techniques (Kasjono et al, 2023;Odoardi et al, 2023;Sunarti et al, 2023). This research discovered that social capital, which includes elements like community initiative, education, communication, and skill development, is significant in waste bank (WB) administration (Ramesh, 2016).…”
Section: Addressing Gaps In Existing Literaturementioning
confidence: 99%
“…The strong connection between social capital and waste management practices highlights the significant role of social networks, trust, and shared standards in promoting a culture of responsible waste management. Studies have indicated that social capital, encompassing elements like human capital and social connections, can impact pro-environmental actions and waste management procedures (Odoardi et al, 2023). Social capital allows community members to share information and work together, which helps decrease harmful emissions from businesses (Ataullah et al, 2023).…”
Section: The Role Of Social Capitalmentioning
confidence: 99%
See 1 more Smart Citation
“…Our control variables are the per capita Gross Domestic Product (gdppro) [50] as a measure of local economic well-being, and the population density per square kilometer (dens), as an increase in population also leads to an increase in waste concentration, hindering its differentiation [51] (Table 1).…”
Section: Datamentioning
confidence: 99%